2008
DOI: 10.1016/j.psyneuen.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Examining cortisol rhythmicity and responsivity to stress in children with Tourette syndrome

Abstract: SUMMARYBackground-Tourette syndrome (TS) is characterized by motor and vocal tics, which are often exacerbated by stress. The hypothalamic-pituitary-adrenocortical (HPA) axis, a major stress response system is thus of interest for understanding TS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 58 publications
5
75
3
Order By: Relevance
“…For example, a series of adult TD patients were found to have elevated levels of cerebrospinal fluid (CSF) norepinephrine and to have excreted high levels of urinary norepinephrine in response to the stress associated with a lumbar puncture (Chappell et al 1994). These elevated levels of CSF norepinephrine may also contribute to the elevation in CSF corticotropin-releasing factor and peripheral cortisol levels seen in some TD patients (Chappell et al 1996;Corbett et al 2008). …”
Section: Noradrenergic Systemmentioning
confidence: 99%
“…For example, a series of adult TD patients were found to have elevated levels of cerebrospinal fluid (CSF) norepinephrine and to have excreted high levels of urinary norepinephrine in response to the stress associated with a lumbar puncture (Chappell et al 1994). These elevated levels of CSF norepinephrine may also contribute to the elevation in CSF corticotropin-releasing factor and peripheral cortisol levels seen in some TD patients (Chappell et al 1996;Corbett et al 2008). …”
Section: Noradrenergic Systemmentioning
confidence: 99%
“…Clinical observations as well as studies of TD and early-onset OCD have consistently suggested that these disorders are sensitive to psychosocial stress (Bornstein et al 1990;Chappell et al 1994;Charmandari et al 2003;Hoekstra et al 2004). For example, a number of reports documented an abnormal response to stress in TD patients (Chappell et al 1996;Lin et al 2007;Corbett et al 2008). Recently, Lin et al (2009) monitored 45 children with tic disorder and/or OCD and 41 matched healthy control subjects over a 2-year period for the level of psychosocial stress.…”
Section: The Role Of Psychosocial Stressmentioning
confidence: 99%
“…Furthermore, evening cortisol values were negatively correlated with overall tic severity 1 . This is relevant to our cases, as Weiner et al revealed a significant decrease in nocturnal cortisol production after use of fluticasone in patients with mild-to-moderate asthma who had not used inhaled corticosteroids (ICS) for at least three months 2 .…”
Section: Discussionmentioning
confidence: 94%
“…Corbett et al studied salivary cortisol levels in children 7-13 years with TS compared to healthy controls and discovered that the TS group had significantly lower evening cortisol levels compared to the control group 1 . Furthermore, evening cortisol values were negatively correlated with overall tic severity 1 .…”
Section: Discussionmentioning
confidence: 99%